Tamarind Turmeric Drink on Menstrual - Masuroh; Shinta, Novelia; J Wowor, Tommy (Rajaki of Tulip Medika Publisher, 2023)
Background: During the menstruation, most of women experience menstrual disorder starting from light, medium, to sever pain. One of the ways to overcome the pain is drinking tamarind turmeric decoction. Objective: The research aims to determine the effect of tamarind turmeric decoction to decrease the pain level of dysmenorrheal pain among female students of Ciruas Junior High School 3, in Serang, Banten. Methodology: This was experimental research with quasy eksperimen (pre dan post test design. The research used paired-Test with the rate significance p= 0.000. There were 40 respondents who suffer from dysmenorrheal pain as the samples. The tamarind turmeric decoction was consumed one glass a day or 220 ml a day for to days. Result: Before drinking tamarind turmeric decoction, the pain level was 14 experienced mild pain (35%), 24 experience medium pain (60%), and experience 2 severe pain (5%). After drinking it, the pain level as 28 experience mild pain (70%), 12 experience medium pain (30%). The result shows that there was a decrease of pain level after the intervention. The result of statistical test was p=0,000 (p<0,05). It shows that there was a significant effect of consuming tamarind turmeric decoction to decrease dysmenorrheal pain level among female students of Ciruas Junior High School 3, Serang, Banten. Conclusion and Suggestion: Tamarind turmeric decoction helps reducing dysmenorrheal pain. Female student needs to consume the decoction to overcome the menstrual pain.